Historical SST warming events in the Northeastern Pacific: How unique is the Warm Blob? - Ramos-Rodríguez, Alejandro; González-Rodríguez, Eduardo; Villalobos, Héctor; Soldatini, Cecilia; Romero-Vadillo, Eleonora (Revista de Biología Marina y Oceanografía, 2020)
During 2013-2015 a patch of warm water called Warm Blob appeared in the northeastern Pacific, producing several effects at biological and physical level. This event appears to be unique, however, evidence was encountered for another three events similar to the recent Warm Blob event during the period from 1854 to 2017 through analyzing the historical anomalies of the SST anomalies in the Pacific Ocean. Each event showed the same distinctive Warm Blob spatial pattern —firstly, a patch of warm water develops in the northern Pacific south of Alaska, and gradually spreads southward along the coast reaching up to Baja California Peninsula”. During the 2013-2015 event, this warm water patch raised the seawater temperature anomalies above 0.5 °C, with a maximum of 4 °C. The other past events obtained in the time series analysis occurred in 1874, 1936 and 1962 and lasted around 18-24 months each. Each warming event is described, showing that the most intense was the 2013-15, followed by the 1935-36. The results suggest a periodicity of occurrence of 25 to 60 years that can also be traced on the biology of the region. These findings propose that such warmings are part of the climatic variability in the northeastern Pacific and should be studied with more detail to determine its cause.